Theology of Disability in the Local Church From Compassion to Participation as Imago Dei - Sibagariang, Monika (Cattleya Darmaya Fortuna, 2024)
The Christian Church in Indonesia often faces challenges in fully including people with disabilities—both in worship, ministry, and faith communities. This article aims to develop a theological framework for disability that moves from a paradigm of mercy to a paradigm of active participation, with the conceptual foundation that all human beings—including people with disabilities—are imago Dei (the image of God). Using a practical-contextual theology approach, this research examines the local church context in Indonesia, analyzes biblical literature and Christian theological traditions, and examines field studies on inclusion in worship and ministry for congregations with disabilities. The results of the study indicate that in many church communities, people with disabilities are still treated merely as objects of mercy or altruistic service, rather than as subjects of faith with equal rights and responsibilities. This is rooted in the paradigm of normalism and the social stigma against “disability.” Through biblical reading (including stories of Jesus involving people with disabilities) and theological reflection on the imago Dei, this article asserts that people with disabilities must be seen as full participants in worship, church life, and missionary service. The proposed theological framework consists of three main components: recognition of dignity, active participation, and community transformation. First, the recognition of dignity means that people with disabilities possess spiritual dignity and identity in Christ that is not diminished by physical or mental conditions. Second, active participation requires changes in church structures, liturgy, and ministries so that inclusivity becomes real—not merely symbolic. Third, community transformation focuses on renewing congregational culture to truly embrace diversity as part of the body of Christ. These findings confirm that disability theology is not merely a social or pastoral theme, but an integral part of Christian theology that reflects the reality of salvation and an inclusive community of faith. Thus, the local church in Indonesia is invited to reject passive compassion and replace it with a theological and practical commitment to true inclusion. This article contributes to the development of a practical theology oriented toward justice, participation, and human dignity in diverse ecclesial contexts.